Analisis Kemampuan Pemecahan Masalah Matematis Siswa Kelas IV Materi Bangun Datar Berdasarkan Teori Polya - Khasanah, Uswatun; Rahayu, Ratri; Ristiyani, Ristiyani (Didaktika, 2021)
This research aimed to analysize mathematical problem-solving abilities in plane figure material based on his Polya’s theory in fourth-grade students of SDN 5 Kalipucang Kulon. This research is based on test and interview results which show that mathematical problem-solving skills of fourth grader was still low. Problem solving skills is real effort in order to find for way out or idea related to goals to be achieved. Mathematical problem-solving indicator according to Polya’s theory are four stages, including: (a) understanding the problem, (b) devising a plan, (c) carrying out the plan, and (d) looking back. This research used descriptive qualitative design. The participants were 6 fourth-graders by high, medium, and low categories. The researcher collected the data by documentation of problem-solving ability test and interview. Data analysis techniques used were data reduction, data presentation, and drawing a conclusion. The research result showed that (1) students with high category were able to understand the problem, devisie and carry out the plan, and look back according to Polya’s stage. (2) Medium category students were only capable to understand the problem, devise and carrying out the plan, but unable to do looking back. (3) Low category students face a difficulty in understanding the problem, can not write completion plan and do the calculation, and also unable to look back the answer. This research suggested to teachers to be able to accompany and provide special attention to low grade students problem-solving ability in facing the story questions, and should getting used to students in a way introduce story questions related to daily life so that students will get used to face problem in mathematical study.